2016
DOI: 10.1007/s11524-016-0039-8
|View full text |Cite
|
Sign up to set email alerts
|

Local Actors’ Frames of the Role of Living Conditions in Shaping Hypertension Risk and Disparities in a Colombian Municipality

Abstract: Conditions in the social and physical environment influence population health and risk for CVD, including hypertension. These environmental conditions are influenced by the decisions of public officials, community leaders, and service providers. Examining the frames that local decision makers bring to understanding hypertension can provide important insights into the decisions that they make about strategies for addressing this problem in their jurisdiction. The goal of this study was to examine the frames tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
0
4
1
4
Order By: Relevance
“…Por otro lado, por sí mismos han jugado un papel determinante sobre el estado de salud de las minorías étnicas en Colombia. En un estudio cualitativo llevado a cabo en la ciudad de Quibdó, una región con alta concentración de afrocolombianos en Colombia ratifica lo descrito, dado que muestran que factores estructurales como el desempleo o la inseguridad pueden determinar el riesgo de HTA y generar disparidades en salud 40 .…”
Section: Discussionunclassified
“…Por otro lado, por sí mismos han jugado un papel determinante sobre el estado de salud de las minorías étnicas en Colombia. En un estudio cualitativo llevado a cabo en la ciudad de Quibdó, una región con alta concentración de afrocolombianos en Colombia ratifica lo descrito, dado que muestran que factores estructurales como el desempleo o la inseguridad pueden determinar el riesgo de HTA y generar disparidades en salud 40 .…”
Section: Discussionunclassified
“…A qualitative study carried out in Quibdó in 2012 identified forced displacement, unemployment, and unplanned urban space as social determinants of hypertension (20). Participants in that study described those determinants influence urban living conditions for Quibdó’s residents (e.g.…”
Section: Local Contextmentioning
confidence: 99%
“…CHRG convened a meeting with representatives of organizations identified through the above process that expressed interest in joining the coalition. Findings from the qualitative study (20) described above were presented and discussed, with 12 organizations subsequently committing to participate in the coalition to address SDH in Quibdó. Of these, eight represented community groups, three were governmental, and one was academic.…”
Section: Formation and Early Implementation Of The Coalitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its occurrence globally is increasing, and projections estimate a 30% increase in its prevalence by 2025 ( Kearney et al, 2005 ). Low and middle-income countries like Colombia are at higher risk for hypertension ( Sánchez et al, 2009 ), possibly due to factors such as socio-economic inequalities, poor environmental conditions, increasing trends in unhealthy behaviors, and excessive body weight, aging population, and deficient primary health care strategies ( Lucumi et al, 2016 , 2017 ; Sánchez et al, 2009 ; Sarki et al, 2015 ). In Latin America countries, hypertension prevalences are high, being the countries with the highest prevalence: Brazil (25–35%), Paraguay (34%), Chile (33.7%), Uruguay and Venezuela (33%) ( Sánchez et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%